Olfactory LOVER: behavioral and neural correlates of autobiographical odor memory - Larsson, Maria; Willander, Johan; Karlsson, Kristina; Arshamian, Artin (Frontiers in Psychology, 2014)
Autobiographical memories (AMs) are personally experienced events that may be localized in time and space. In the present work we present an overview targeting memories evoked by the sense of smell. Overall, research indicates that autobiographical odor memory is different than memories evoked by our primary sensory systems; sight and hearing. Here, observed differences from a behavioral and neuroanatomical perspective are presented. The key features of an olfactory evoked AM may be referred to the LOVER acronym - Limbic, Old, Vivid, Emotional, and Rare.